Chronicle of a deceleration foretold: Income inequality in Latin America in the 2010s - Leonardo Gasparini; Guillermo Cruces; Leopoldo Tornarolli (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2015)
After a decade of strong progress toward the goal of reducing the high levels of income disparities, there are clear signs of a deceleration in the pace of inequality reduction in Latin America. This paper argues that the deceleration is the result of two set of reasons. First, several of the driving factors of the fall in inequality in the 2000s have lost strength, due to 'natural' motives; and second, the external conditions faced by the Latin American economies have worsened in the early 2010s, making further reductions in inequality more difficult.
Keywords: D63; I31; J11; J21; J31; J82; N36; 330; inequality; income; distribution; Latin America